Orta Doğulu Lisans Öğrencilerinin Gözünde Bölgesel Liderliğin Geleceği ve Türkiye’nin Durumu - (:unkn) unknown (My University, 2018)
Bu araştırma ülkemizde yaygın olan “Orta Doğu’daki karmaşanın nedeni Batılıların Osmanlı Devletini parçalaması” ve “bölgedeki huzuru, güvenliği yine biz Türkler sağlayabiliriz” algılarının Orta Doğu’daki karşılığını ve Orta Doğuluların ülkemize bakışını belirlemek için yapılmış nicel bir araştırmadır. Bu kapsamda veri toplamak amacıyla Orta Doğu ülkelerinden Türkiye’ye lisans ve lisans üzeri eğitim almaya gelen üniversite öğrencilerine bir anket yapılırken aynı zamanda 21.yy’da değişen Türk dış politikası ve bölgesel hamlelere yönelik literatür taraması yapılmıştır. Elde edilen bulgulara göre Orta Doğulu öğrenciler bölgesel bir lider olarak Türkiye, İran ve Suudi Arabistan’ın ön plana çıkarttıkları görülmektedir. Bu karşılık İran’ı ve Suudi Arabistan’ı lider olarak gören öğrencilerin büyük bir kısmının bölgesel liderin Türkiye olması gerektiğini savundukları görülmüştür.

This research is a quantitative survey to determine the value of the perceptions of “the cause of the chaos in the Middle East is the fact that the western people have broken up the Ottoman State” and “we Turks can provide peace, security in the region” in the Middle East and the viewpoint of the Middle East towards our country. In this context, in order to collect data, while conducting a survey for university students from Middle East countries who come to Turkey to study on undergraduate and graduate degrees, also a literature scanning for ever-changing Turkish foreign policy in the 21st century and regional moves have been made. According to the findings, Middle Eastern students are regarding Turkey, Iran and Saudi Arabia in the forefront as a regional leader. It has been observed that most of the students who have seen Iran and Saudi Arabia as leaders, have argued that the regional leader should be Turkey.
THE FUTURE OF REGIONAL LEADERSHIP AND TURKEY’S POSITION COMPARED TO THE MIDDLE EASTERN UNDERGRADUATE STUDENTS